Herpes Simplex Virus Type 1 Infection of the Central Nervous System: Insights Into Proposed Interrelationships With Neurodegenerative Disorders - Duarte, Luisa F.; Farías, Mónica A.; Álvarez, Diana M.; Bueno, Susan M.; Riedel, Claudia A.; González, Pablo A. (Frontiers in Cellular Neuroscience, 2019)
Herpes simplex virus type 1 (HSV-1) is highly prevalent in humans and can reach the brain without evident clinical symptoms. Once in the central nervous system (CNS), the virus can either reside in a quiescent latent state in this tissue, or eventually actively lead to severe acute necrotizing encephalitis, which is characterized by exacerbated neuroinflammation and prolonged neuroimmune activation producing a life-threatening disease. Although HSV-1 encephalitis can be treated with antivirals that limit virus replication, neurological sequelae are common and the virus will nevertheless remain for life in the neural tissue. Importantly, there is accumulating evidence that suggests that HSV-1 infection of the brain both, in symptomatic and asymptomatic individuals could lead to neuronal damage and eventually, neurodegenerative disorders. Here, we review and discuss acute and chronic infection of particular brain regions by HSV-1 and how this may affect neuron and cognitive functions in the host. We review potential cellular and molecular mechanisms leading to neurodegeneration, such as protein aggregation, dysregulation of autophagy, oxidative cell damage and apoptosis, among others. Furthermore, we discuss the impact of HSV-1 infection on brain inflammation and its potential relationship with neurodegenerative diseases.